THE STATE’S ECONOMIC PROTECTION BY THE CRIMINAL JUSTICE SYSTEM CORRUPTION: A CASE STUDY - Ahmad, Kamri; Thalib, Hambali; Muchtra, Mursyid (Fakultas Hukum Universitas Muhammadiyah Magelang, 2020)
This study aims to identify efforts to protect the state's economic security through the criminal justice system in the case of nickel mining in Malapulu Block, Kabaena Island, Southeast Sulawesi, Indonesia. The Supreme Court has decided the case with decision number 2633 K/Pid/Sus/2018. This research was conducted with a qualitative approach through analysis of the description of the prosecutor's indictment and the judge's decision. The results obtained in the study show that the KPK Prosecutor made a mistake by withdrawing the appeal that had been made. This condition results in the lack of consideration made by judges in decision making. Secondly, legal experts do not provide a difference in the meaning of economic and financial losses for the state in judex factie and judex jurist. Third, the indictment by the public prosecutor has not described the form of crime committed as an extraordinary crime. Fourth, there is negligence in the corporate sentence.